2021
DOI: 10.1111/hex.13233
|View full text |Cite
|
Sign up to set email alerts
|

The manifestation of participation within a co‐design process involving patients, significant others and health‐care professionals

Abstract: Background Despite intentions to increase user participation in the development of health services, the concept of participation and how it unfolds within studies with a participatory design has rarely been addressed. Objective The aim of this study was to describe how user participation manifests itself within a co‐design process involving patients, significant others and health‐care professionals, including potential enablers or barriers. Methods This study was conducted in the context of a co‐design process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(96 citation statements)
references
References 45 publications
3
92
1
Order By: Relevance
“…According to Dent-Spargo (2018), participants in a co-design process are usually motivated to contribute above and beyond their duties when their psychological needs for autonomy, competence, and relatedness are met. Recent work by Lindblom et al (2021) resonates with these findings by adding that although participants may not fully understand their participatory role, they are more motivated to contribute when their insights are valued. Indeed, Riz said that the moral support, affection, and kindness shown by his co-designer partners made him enjoy his work more.…”
Section: Motivation In Working With Co-designersmentioning
confidence: 82%
See 2 more Smart Citations
“…According to Dent-Spargo (2018), participants in a co-design process are usually motivated to contribute above and beyond their duties when their psychological needs for autonomy, competence, and relatedness are met. Recent work by Lindblom et al (2021) resonates with these findings by adding that although participants may not fully understand their participatory role, they are more motivated to contribute when their insights are valued. Indeed, Riz said that the moral support, affection, and kindness shown by his co-designer partners made him enjoy his work more.…”
Section: Motivation In Working With Co-designersmentioning
confidence: 82%
“…They proposed that the participants of a co-design process are motivated to contribute more and even work outside their comfort zone if their psychological needs for autonomy, competence, and relatedness are met. This finding was supported by Lindblom et al's (2021) work which demonstrated that acknowledgement of participants" insights motivates them to contribute more, even if they do not fully understand their role as co-designers.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recent co-produced research recommends implementing costed external training, especially with regard to establishing a relationship from the start [ 68 ].Our PPIE group was diverse with patients and carers with differing levels of PPIE experience. We found this dynamic worked well in terms of assigning roles and responsibilities [ 22 ], and tailoring varied strands of work to specific roles based on preferences enhanced the value of the PPIE in co-design as everyone was treated with equal importance [ 13 , 14 , 68 , 69 ]. Establishing a joint understanding and clarity of roles was central to managing expectations, especially when sometimes we could not feasibly meet preferences for involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the codesign process and the participants have been presented previously. 25 Three areas of unmet needs related to care transitions were identified across patients, significant others, and healthcare professionals: 1. Shared understanding of patient illness and situation.…”
Section: Development Of the Interventionmentioning
confidence: 99%